THE PERFORMANCE OF JAVA AND ONGOLE CROSSBRED BULL UNDER INTENSIVE FEEDING MANAGEMENT - Lestari, C.M.S.; Adiwinarti, R.; Arifin, M.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
This study was set up to evaluate the performance of Java and Ongole Crossbred (OC) bulls fedconcentrate and rice straw. A total of four Java bulls and four OC bulls were used in this experiment. Thebulls were fed concentrates (50% of the total dry matter feed requirement) and rice straw (ad libitum).The concentrates were consisted of rice bran, beer waste product, copra meal, minerals, with crudeprotein (CP) and total digestible nutrients (TDN) contents of 15.32% and 73.09%, respectively. Theaverage daily gain (ADG), dry matter intake (DMI), protein and energy intake, and feed conversion ratio(FCR) were observed. The results of this study showed that the ADG, DMI, CP and TDN intake, andFCR were not significantly different (p> 0.05). The ADG of Java and OC bulls were 0.58 kg and 0.78kg, respectively. The averages of DMI, CP and TDN intake were 6.59 kg (2.09% of BW), 0.81 kg and4.34 kg for Java bulls whereas for OC bulls were 6.42 kg (2.11% of BW), 0.78 kg, and 4.20 kg,respectively. The FCR of Java bulls was 11.49 and those of OC bulls was 9.21. It can be concluded thatJava and OC bulls raised intensively and fed concentrate and rice straw had the similar performance.